Comparative Analysis of Oil and Gas Terms - Mamanazarova Gulhayo Ilhamjanovna (Researchparks Publishing, 2021)
The article deals with the issues based on comparative analysis of oil and gas terms and studying the difficulties which appears while translating. The efficiency of translation largely depends on the accuracy of translation of professional vocabulary, which determines the relevance of this work. The classification of professional vocabulary is given. As a result of the analysis, the lexical features of the translation of oil and gas terms have been determined, the importance of their correct translation has been confirmed.